A-16 More than Total Symptom Severity: Identifying Subtypes of Persistent Post-Concussion Symptoms using Normative Data. (17th August 2022) - Karr, Justin E; Zuccato, Brandon G; Ingram, Eric O; Considine, Ciaran M; Merker, Bradley; Abeare, Christopher A
Abstract: Objective: Prior factor analyses have supported the multidimensionality of post-concussion symptoms, but the symptom total score is often interpreted alone in practice. This study examined the added value of norm-referenced post-concussion symptom subscales to detect different subtypes of symptom presentations following concussion. Method: Adolescent student-athletes (N = 1008; 15.3 ± 1.4 years-old; 66.7% boys) with one or more prior concussions, at least 6 months post injury, completed the Post-Concussion Symptom Scale at preseason baseline. Severity ratings on four symptom subscales (i.e., cognitive, sleep-arousal, physical, and affective) were compared to normative data matched on gender and preexisting health conditions. The frequencies at which participants were elevated on one or more symptom subscales were calculated. Results: In the total sample, 21% of student-athletes were elevated on only one symptom subscale, 11% on two subscales, 8% on three subscales, and 6% on four subscales. Among student-athletes with a single elevated subscale, all symptom domains had similar frequencies of elevation. No differences in symptom elevations were found based on gender or number of prior concussions. Conclusion(s): A single-domain symptom elevation was the most common post-concussion symptom presentation among a cohort of adolescent student-athletes, with 26% of student-athletes elevated on a single subscale but not the total symptom score. These findings indicate that there are subtypes of post-concussion symptom presentations that would be missed through an interpretation of a total symptom severity score alone.